Water Flow Monitoring and Automation in Agriculture Field - Felci, C; SenthilRajan, A (International Journal of Computer Sciences and Engineering, 2019)
Smart Agriculture helps to reduce wastage, effective usage of fertilizer and thereby increase the crop yield. In this work, a system is developed to monitor crop-field using sensors (soil moisture, temperature, humidity) and automate the irrigation system. Our main objective of this work is to for Farming where various new technologies to yield higher growth of the crops and their water supply. Automated control features with latest electronic technology using microcontroller which turns the pumping motor ON and OFF on detecting the dampness content of the earth and GSM phone line is proposed after measuring the temperature, humidity, and soil moisture. The irrigation is automated if the moisture and temperature of the field falls below the brink. The notifications are sent to farmers’ mobile periodically. The farmers’ can able to monitor the field conditions from anywhere. This system will be more useful in areas where water is in scarce. This system is 92% more efficient than the conventional approach.